Indonesia Arahan Pengembangan Agroindustri di Kawasan Perkotaan Pangkalan Banteng Kabupaten Kotawaringin Barat - Fadrian, Fadrian (Fakultas Teknik Universitas Bosowa, 2024)
The purpose of this study was to find out how the Agro-industrial Development Directions in the Urban Area of ​​Pangkalan Banteng, West Kotawaringin Regency and to provide efforts to exploit the potential of industrial area designation in agriculture which has a direct impact on increasing regional economic income as well as opportunities to create jobs for the community. The analytical method used is the analysis of the carrying capacity of the land which refers to (Permen PU No 20 Year, 2007) and also uses a qualitative descriptive analysis, where data is obtained from survey results and interviews. The results of this study found that in the West Kotawaringin Regency regional regulation regarding regional spatial planning no. 1 of 2018 Pangkalan Banteng was designated as an area supporting the strategy of economic growth in agriculture. As a supporting area for an economic growth strategy in agriculture, it needs to be supported by the designation of agro-industrial areas as a processing facility to exploit the potential of the area, but the urban base of Banten itself in the regional regulation regarding the urban spatial plan of the bull base has not yet determined the location of the designation.